Bone cement-augmented vs. conventional pedicle screws for osteoporotic lumbar spondylolisthesis: a meta-analysis - Qin, Guoyi; Hu, Lihui; Liang, Zhaoming; Li, Jinghuai; Bao, Xiaohang; Lin, Shaohu; Wang, Yicheng; Zhong, Yuanming (Frontiers in Surgery, 2026)
BackgroundIn patients with lumbar spondylolisthesis complicated by osteoporosis, conventional pedicle screw internal fixation often leads to complications such as screw loosening and fixation failure due to low bone mineral density. Bone cement-augmented pedicle screw technology has been widely used to enhance screw stability; however, its efficacy and safety in lumbar spondylolisthesis lack systematic evaluation.ObjectiveTo systematically evaluate the clinical efficacy and safety of bone cement-augmented pedicle screws vs. conventional pedicle screws in the treatment of osteoporotic lumbar spondylolisthesis.MethodsRelevant literatures were retrieved from databases including PubMed, Cochrane Library, EMbase, Web of Science, CNKI, Wanfang, VIP, and SinoMed from their inception to July 2025. Retrospective cohort studies or randomized controlled trials were included. Two researchers independently screened literatures, extracted data, and assessed the risk of bias. Meta-analysis was performed using RevMan 5.4 software.ResultsA total of 9 studies involving 850 patients were included. Meta-analysis results showed that compared with the conventional screw group, the bone cement-augmented screw group had significantly better outcomes in terms of the last follow-up Visual Analogue Scale (VAS) score (MD = −0.15, 95% CI: −0.22 to −0.08, P < 0.0001), Oswestry Disability Index (ODI) score (MD = −2.36, 95% CI: −3.98 to −0.75, P = 0.04), intervertebral space height (MD = 1.99, 95% CI: 0.73–3.25, P = 0.002), screw loosening rate (OR = 0.18, 95% CI: 0.09–0.38, P < 0.0001), and intervertebral fusion rate (OR = 3.98, 95% CI: 2.36–6.73, P < 0.0001). The operation time in the bone cement-augmented group was longer (MD = 32.13, 95% CI: 14.30–49.95, P = 0.0004); however, there were no significant differences in intraoperative blood loss, length of hospital stay, or complication rate between the two groups.ConclusionBone cement-augmented pedicle screws can significantly improve pain, functional status, intervertebral fusion rate, and screw stability in patients with osteoporotic lumbar spondylolisthesis. Although it prolongs the operation time, it does not increase the risk of intraoperative bleeding or complications, thus holding favorable clinical application value.